Razão e proporção : suas diversas alternativas nas resoluções de problemas - Lima Neto, José Ferreira (2023)
In this work, we present a methodological proposal for the teaching of specific and recurrent questions in entrance exams and public contests on the subject of ratio and proportion, seeking to allow the student two different perceptions about a same problem: traditional method and the method proposed by the author of this work. We divided these issues and problem situations into four groups: problems with fractions, problems with ratio and proportion, problems with the compound rule of three and percentage problems. Furthermore, in order to prepare the reader for a better understanding of our proposal, we show in each topic, the theory objective so that he understands the resolutions through the two methods, as well as six Worked examples of each method for each topic worked on. At the end of each theme, we conducted an opinion poll with ten students, in order to expose their understandings with the resolution of an issue through the two methods and thus define the strengths and weaknesses of each one from their respective points of view.